Rational synthesis of MoS2 nanosheet arrays on carbon fibres for sodium ion storage. (23rd August 2020) - Liang, Xinqi; Chen, Minghua; Shen, Shenghui; Xia, Xinhui
Abstract: Rational synthesis of advanced anode materials is vital in developing high-performance sodium ion batteries. In this work, we report a facile hydrothermal strategy for construction of carbon fibre cloth (CFC) supported MoS2 nanosheet arrays. Interconnected NoS2 nanosheets of 5–10 nm are uniformly grown on the surface of CFC forming arrays structure. Good adhesion and high porosity are obtained in the CFC/MoS2 arrays. When evaluated as anodes of sodium ion batteries, the CFC/NoS2 arrays deliver a high specific capacity of 413 mAh g −1 at a current density of 0·5 A g −1, and 176 mAh g −1 at a current density of 3 A g −1 . Additionally, good rate performance and cycling life are proven for the CFC/MoS2 arrays. The good performance is ascribed to the CFC network and arrays architecture. Our synthetic method can be used for fabrication of other advanced metal sulfides anodes for sodium ion batteries. Abstract : uf0001 Carbon fibre cloth (CFC) supported MoS2 arrays electrodes are synthesized via a hydrothermal method and exhibit a noticeable electrochemical performance as anode of sodium ion batteries.